Negative Exponents (Negative Indices)


Consider the following division:
$$\dfrac{3^2}{3^3} = 3^{2-3} = 3^{-1}$$
Now, if we attempt to calculate the value of this division:
$$\dfrac{3^2}{3^3} = \dfrac{9}{27} = \dfrac{1}{3}$$
From this conclusion we can say that $3^{-1} = \dfrac{1}{3}$.
This conclusion can be generalised:
$$a^{-1} = \dfrac{1}{a}$$

Example 1

Write $4^{-1}$ in fractional form.

$4^{-1} = \dfrac{1}{4}$

Example 2

Write $\dfrac{1}{x}$ in exponent (index) form.

$\dfrac{1}{x} = x^{-1}$

This rule can be extended for negative exponents (negative indices) other than $-1$.
Consider the expression $\dfrac{a^2}{a^5}$.
Using the exponent laws $\dfrac{a^2}{a^5} = a^{2-5} = a^{-3}$ and simplifying the fraction, we obtain
\( \begin{align} \displaystyle \require{cancel}
\dfrac{a^2}{a^5} &= \dfrac{\bcancel{a} \times \bcancel{a}}{\bcancel{a} \times \bcancel{a} \times a \times a \times a} = \dfrac{1}{a^3}. \\
\end{align} \)

Thus $a^{-3} = \dfrac{1}{a^3}$.
In general we are able to say:
$$a^{-n} = \dfrac{1}{a^n}$$

Example 3

Write $5^{-2}$ in fractional form.

$5^{-2} = \dfrac{1}{5^2} = \dfrac{1}{25}$

Example 4

Write $\dfrac{1}{a^3}$ using negative exponents (negative indices).

$\dfrac{1}{a^3} = a^{-3}$


Algebra Algebraic Fractions Arc Binomial Expansion Capacity Common Difference Common Ratio Differentiation Double-Angle Formula Equation Exponent Exponential Function Factorials Factorise Functions Geometric Sequence Geometric Series Index Laws Inequality Integration Kinematics Length Conversion Logarithm Logarithmic Functions Mass Conversion Mathematical Induction Measurement Perfect Square Perimeter Prime Factorisation Probability Product Rule Proof Pythagoras Theorem Quadratic Quadratic Factorise Rational Functions Sequence Sketching Graphs Surds Time Transformation Trigonometric Functions Trigonometric Properties Volume




Your email address will not be published. Required fields are marked *